Co-production of ethanol and polyhydroxybutyrate from lignocellulosic biomass using an engineered Saccharomyces cerevisiae - Tran, Phuong Hoang Nguyen; Jung, Je Hyeong; Ko, Ja Kyong; Gong, Gyeongtaek; Um, Youngsoon; Lee, Sun-Mi (Pergamon Press Ltd., 2023)
The development of glucose/xylose co-fermenting Saccharomyces cerevisiae has improved bioethanol yield from lignocellulosic biomass, the most abundant and sustainable resource for net-zero production of fuels and chemicals. The co-production of value-added chemicals would further improve the economic feasibility of lignocellulosic bioethanol production. Here, we developed a glucose/xylose co-fermenting S. cerevisiae strain capable of co-producing polyhydroxybutyrate, a prominent biodegradable polymer, as an intracellularly accu-mulated co-product by introducing a polycistronic polyhydroxybutyrate biosynthetic pathway. The engineered strain accumulated polyhydroxybutyrate with a content of 64 mg/g DCW while maintaining extracellular pro-duction of ethanol with a high yield (0.43 g ethanol/g sugar). The co-production of ethanol and poly-hydroxybutyrate was then evaluated using various types of biomass, including sugarcane bagasse, silver grass, and even cardboard boxes. This study demonstrates the feasibility of co-production of bioethanol and value-added chemicals to maximize the values derivable from lignocellulosic biomass.